Pengaruh Proporsi Komisaris Independen, Leverage, Sales Growth, Dan Profitabilitas Pada Tax Avoidance - Ayuningtyas, Ni Putu Winda; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p10, 2018)
This study aims to examine the variables of the proportion of independent commissioners, leverage, sales growth and profitability that affect companies to carry out tax avoidance. This research was conducted on all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014-2017, with a total of 200 samples. Sample selection using probability sampling technique is purposive sampling technique. The data analysis technique used is a multiple linear regression analysis test. The results showed that the proportion of independent commissioners, sales growth and profitability had no effect on tax avoidance while leverage had an effect on tax avoidance. Keywords: tax, leverage, sales growth, profitability